Tumor Hypoxia Drives Genomic Instability - Tang, Ming; Bolderson, Emma; O’Byrne, Kenneth J.; Richard, Derek J. (Frontiers in Cell and Developmental Biology, 2021)
Cancer is a leading cause of death worldwide. As a hallmark of cancer, hypoxia is associated with poor prognosis due to enhanced tumour malignancy and therapeutic resistance. The enhanced tumour aggressiveness stems at least partially from hypoxia-induced genomic instability. Therefore, a clear understanding of how tumour hypoxia induces genomic instability is crucial for the improvement of cancer therapeutics. This minireview summarises recent developments highlighting the association of tumour hypoxia with genomic instability and the mechanisms by which tumour hypoxia drives genomic instability, followed by how hypoxic tumours can be specifically targeted to maximise efficacy.